Kommentar zu den simonideischen Versinschriften - Petrovic, Andrej. (Mnemosyne, bibliotheca classica Batava. Supplementum,, 2007)
The work concerns 15 epigraphic and/or verse inscriptions, handed down from the writers of the 5th and 4th centuries BC. These inscriptions were probably commissioned from Simonides of Keos. The commentaries on the individual verse inscriptions form the centre of the investigation. Each commentary is introduced by a text for the sake of orientation concerning the epigram in question, by a brief apparatus criticus, and by a review of the relevant secondary literature. The historic, literary, and, when possible, architectural contexts are taken into consideration in the interpretations. The first part of the book includes studies on the archaic and classical epigram in the public space, on the sources and transmissions of the oldest Simonidean verse inscriptions, and on the status quaestionis regarding the authenticity of the claims of authorship. The concluding observations deal with epigrammatic competitions and with the historical reception of the verse inscriptions in the public space. Die Arbeit widmet sich 15 epigraphisch und/oder bei Autoren des 5. und 4. Jhs. volume Chr. überlieferten Versinschriften, die vermutlich bei Simonides von Keos in Auftrag gegeben wurden. Den Kern der Untersuchung bilden die Kommentare zu einzelnen Versinschriften. Ein zur Orientierung gedachter Text des jeweiligen Epigramms, ein knapper kritischer Apparat und ein Überblick über die Sekundärliteratur leiten die einzelnen Kommentare ein. In der Deutung werden die historischen, literarischen und, wenn möglich, architektonischen Kontexte berücksichtigt. Der erste Teil des Buches umfasst Studien zum archaischen und klassischen Epigramm im öffentlichen Raum, zu den Quellen und zur Überlieferung der ältesten simonideischen Versinschriften und zum status quaestionis bezüglich der Zuschreibungen. Der abschließende Ausblick gilt epigrammatischen Wettbewerben und der historischen Rezeption der Versinschriften im öffentlichen Raum.